FROM IDEA TO PRODUCT IN HEALTHCARE: TRANSFORMING SECTOR NEEDS INTO INNOVATIVE TECHNOLOGICAL SOLUTIONS - Bandeira Brasiliano, Bruno (Humanas em Perspectiva, 2026)
The healthcare sector, characterized by high complexity, intense regulation, and constant demand for therapeutic and operational advancements, presents unique challenges for technological innovation. As evidenced by Topol (2019), transforming clinical and operational needs into innovative solutions is fundamental for improving health outcomes, increasing system efficiency, and democratizing access to medical care. This article analyzes the process of designing, developing, and implementing technological innovations in the healthcare sector, with emphasis on critical factors that drive real impact on business and society.